2022
DOI: 10.1039/d2nr02150a
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose exposure to phytosynthesized gold nanoparticles combined with glutamine deprivation enhances cell death in the cancer cell line HeLa via oxidative stress-mediated mitochondrial dysfunction and G0/G1 cell cycle arrest

Abstract: Cancer cells use nutrients like D-glucose (Glc) and L-glutamine (Q) more efficiently for their development. This increased nutritional dependency of malignant cells has been commonly employed in various in vitro...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…This happens due to the production of ROS induced by AgNPs which inhibits ATP synthesis and subsequently damaging the DNA [ 59 ]. Oxidative stress caused by NPs have been reported to induces mitochondrial dysfunction which suppress the division of cancerous cells [ 60 ] In this assay, cells were treated with the synthesized AgNPs (200 μg/ml) for 24hrs. In cytotoxicity of HepG2 cell lines by AgNPs (200 μg/ml) exhibited strong activity by S-AgNPs (83.82%), followed by RS-AgNPs (74.55%) and R-AgNPs (44.82%) ( Fig 8B, 8C ).…”
Section: Resultsmentioning
confidence: 99%
“…This happens due to the production of ROS induced by AgNPs which inhibits ATP synthesis and subsequently damaging the DNA [ 59 ]. Oxidative stress caused by NPs have been reported to induces mitochondrial dysfunction which suppress the division of cancerous cells [ 60 ] In this assay, cells were treated with the synthesized AgNPs (200 μg/ml) for 24hrs. In cytotoxicity of HepG2 cell lines by AgNPs (200 μg/ml) exhibited strong activity by S-AgNPs (83.82%), followed by RS-AgNPs (74.55%) and R-AgNPs (44.82%) ( Fig 8B, 8C ).…”
Section: Resultsmentioning
confidence: 99%
“…The cells were seeded into 96-well plates at a density of 5000–10,000 cells per well. After 24 h, cells were washed with PBS buffer and treated with 100 μM DCFH-DA for 1 h [ 52 ]. Cells were again washed with PBS and treated with the IC 50 concentration of PTAgNPs and untreated wells were considered as the control.…”
Section: Methodsmentioning
confidence: 99%
“…[80,81] Therefore, 1 mM AgNO 3 concentration was accepted as the optimum concentration for the biosynthesis of small-size HP-AgNPs and corroborating the results of Azmi et al [82] Silver nanoparticle synthesis is a pH-dependent reaction by altering the electrical load of phytochemicals and ultimately influences the capping and stabilizing capacity of Ag ions. [83] In the current work, the pH 5, 6, 7, 8, 9, 10, 11, and 12 were chosen for the optimization of HP-AgNPs fabrication. The results suggested that no UV absorption peaks appeared at lower pH (5 and 6), showing that an acidic medium is not appropriate for NPs synthesis.…”
Section: Discussionmentioning
confidence: 99%